Application of big data and business analytics - Kumari, Sneha; Tripathy, K. K.; Kumbhar, Vidya (Bingley, U.K. : Emerald Publishing Limited, 2020)
Application of Big Data and Business Analytics uses advanced analytic tools to explore the solutions to problems in society, environment and industry. The chapters within bring together researchers, engineers and practitioners, encompassing a wide and diverse set of topics in almost every field.
Prelims -- Chapter 1: Data analytics for soil health management and their crop mapping in Satara district -- Chapter 2: Analytics in metal sustainability: recovery of non-renewable resources using low-cost biomaterials -- Chapter 3: Use of business analytics and GIS for dematerialization of land bank in India and its benefits -- Chapter 4: Using Google trends in modeling product demand and consumption: case of UK apparel and footwear demand -- Chapter 5: Applications of big data analytics: a boon for the food industry -- Chapter 6: Importance of data analytics in international trade: a case of Indian cotton -- Chapter 7: Data management in India: a case study of Aadhaar project -- Chapter 8: Customer segmentation using RFM analysis: real case application on a fuel company -- References -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Big data -- Industrial applications; Big data -- Scientific applications; Business planning -- Statistical methods; Computers, Data Science -- General; Business applications